Palaces and Courts of the Exposition : A Handbook of the Architecture, Sculpture and Mural Paintings, with Special Reference to the Symbolism - James, Juliet Helena Lumbard, 1864- (Salt Lake City, UT : Project Gutenberg, 2004)
"Palaces and Courts of the Exposition" by Juliet Helena Lumbard James is a handbook rich with architectural detail, artistic analysis, and symbolism, likely crafted during the early 20th century. This work captures the grandeur of the exposition through extensive descriptions of the palatial architecture, sculptures, and mural paintings, celebrating a significant cultural and historical event. The text likely addresses themes of human achievement, progress, and artistic convergence, reflecting on how these grand displays of artistry come together to create a shared cultural heritage. The beginning of this handbook paints an evocative picture of a stunning city by the sea, filled with imaginative references to figures such as Venus and the Spirits of Enterprise and Energy who bring forth a beautifully pastel-colored cityscape. The foreword sets a tone of awe and anticipation for the exposition, suggesting that the reader will be transported into a world where art and architecture fuse into a celebration of civilization's achievements. The opening also hints at an exploration of various palaces and courts, crafted by reputed architects and artists, indicating a journey through symbolic representations of industry, nature, and humanity central to the exposition. (This is an automatically generated summary.)
Release date is 2004-05-01
This eBook was prepared by David Schwan
Keywords: Panama-Pacific International Exposition (1915 : San Francisco, Calif.)